Multiple-Aperture-Based Solar Seeing Profiler. (4th January 2016) - Ren, Deqing; Zhao, Gang; Zhang, Xi; Dou, Jiangpei; Chen, Rui; Zhu, Yongtian; Yang, Feng
Abstract: Characterization of day-time atmospheric turbulence profiles up to 30 km above the telescope is crucial for designs and performance estimations of future solar multiconjugate adaptive optics (MCAO) systems. Recently, the S-DIMM+ method has been successfully used to measure the vertical profile of turbulence. However, to measure profile up to 30 km employing the S-DIMM+ method, a telescope with a diameter of at least 1.0 m is needed, which restricts the usage of S-DIMM+, since large telescopes are scarce and their time is limited. To solve this problem, we introduce the multiple-aperture seeing profiler (MASP), which consists of two portable small telescopes instead of a single large aperture. Numerical simulations are carried out to evaluate the performance of MASP. We find that for one layer case, MASP can retrieve the seeing with error ∼5% using 800 frames of wavefront sensor (WFS) data, which is quite similar to the results of a telescope with diameter of 1120 mm. We also simulate profiles with four turbulence layers, and find that our MASP can effectively retrieve the strengths and heights of the four turbulence layers. Since previous measurements at Big Bear Solar Observatory showed that day-time turbulence profile typically consists of four layers, the MASP we introduced is sufficient for actual seeing measurement.